Disparity in Mortality From Rheumatic Heart Disease in Indigenous Australians. Issue 7 (July 2015) - Colquhoun, Samantha M.; Condon, John R.; Steer, Andrew C.; Li, Shu Q.; Guthridge, Steven; Carapetis, Jonathan R.
Abstract : Background: Recent estimates of the global burden of rheumatic heart disease (RHD) have highlighted the paucity of reliable RHD mortality data from populations most affected by RHD. Methods and Results: We investigated RHD mortality rates and trends for Indigenous and non‐Indigenous Australians in the Northern Territory (NT) for the period 1977–2005 and seminationally (NT plus 4 other states, covering 89% of Indigenous Australians) from 1997 to 2005 using vital statistics data. All analysis was undertaken by Indigenous status, sex, and age at death. In the NT, 90% of all deaths from RHD were among Indigenous persons; however, the Indigenous population makes up only 30.4% of the NT population. The death rate ratio (Indigenous compared with non‐Indigenous) was 54.80 in the NT and 12.74 in the other 4 states (estimated at the median age of 50 years). Non‐Indigenous death rates were low for all age groups except ≥65 years, indicating RHD deaths in the elderly non‐Indigenous population. Death rates decreased at a more rapid rate for non‐Indigenous than Indigenous persons in the NT between 1997 and 2005. Indigenous persons in other parts of Australia showed lower death rates than their NT counterparts, but the death rates for Indigenous persons in all states were still much higher than rates for non‐Indigenous Australians. Conclusions: Indigenous Australians are much more likely to die from RHD than other Australians. Among the Indigenous population, RHD mortality is much higher in the NT than elsewhere in Australia, exceeding levels reported in many industrialized countries more than a century ago. With the paucity of data from high‐prevalence areas, these data contribute substantially to understanding the global burden of RHD mortality.